Development of ZnCdSe/ZnS quantum dot-based fluorescence immunochromatographic assay for the rapid visual and quantitative detection 25⁃hydroxyvitamins D in human serum - Wang, Jianfa; Sun, Guoshao; Li, Fang; Zhu, Zhi; Sun, Lei; Lv, Pengju; Yue, Han (Frontiers in Bioengineering and Biotechnology, 2023)
Vitamin D deficiency is associated with various diseases such as obesity, digestive problems, osteoporosis, depression, and infections, and has therefore emerged as a topic of great interest in public healthcare. The quantitative assessment of 25-hydroxyvitamin D (25-OH VD) in human serum may accurately reflect the nutritional status of vitamin D in the human body, which is significant for the prevention and treatment of vitamin D-deficient patients. In this study, we developed an assay for quantitative detection of 25-OH VD based on the 25-OH VD monoclonal antibody (mAb), and identified the optimal process parameters. The following process settings were found to be suitable for the test strips: pH of 7.6, 1-Ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) ratio of 1:2000, and the anti-25-OH VD mAb ratio was 1:8. The equilibration time of the immune dynamic assay was 15 min. Under optimal conditions, the quantum dot nanoparticle-based fluorescent immunochromatographic assay (QDs-FICA) exhibited dynamic linear detection of 25-OH VD in PBS, from 5 ng/mL to 100 ng/mL, and the strip quantitative curve could be represented by the following regression equation: y=−0.02088 log (x)+1.444 (R2=0.9050). The IC50 of the QDs-FICA was 39.6±1.33 ng/mL. The specificity of the QDs-FICA was evaluated by running several structurally related analogues, including 25-OH VD2, 25-OH VD3, 1,25-OH2VD3, 1,25-OH2VD2, VD2, and VD3. The coefficients of variation were all below 10%. The shelf life of the test strips in this study was about 160 days at room temperature. Briefly, this study is the first to perform QDs-FICA for the rapid visual and quantitative detection of 25-OH VD, with great potential significance for clinical diagnosis of vitamin D-associated diseases.